Hubungan Iklim Organisasi dengan Kinerja Pegawai di Kantor Dinas Pariwisata Pemuda dan Olahraga Kota Bukittinggi - Miftahul Jannah; Nellitawati Nellitawati; Ermita Ermita; Yulianto Santoso (Universitas Negeri Padang, 2022)
This research is motivated by the results of the author's observations while carrying out Field Management Practices at the Office of Tourism, Youth and Sports of Bukittinggi City which shows that employee performance is still not optimal. Many factors affect employee performance. One of them is organizational climate. The purpose of this study was to obtain data and information about 1) organizational climate, 2) employee performance and 3) the relationship between organizational climate and employee performance at the Office of Tourism, Youth and Sports, Bukittinggi City. The hypothesis proposed in this study is that there is a significant relationship between organizational climate and employee performance. This study is a correlation study, aiming to see the relationship between organizational climate and employee performance at the Office of Tourism, Youth and Sports, Bukittinggi City. The population of this study is all civil servants who work at the Office of Tourism, Youth and Sports of Bukittinggi City with a total of 65 people. The research sample was taken using the Proportional Stratified Random Sampling technique with the Cochran formula so that the sample in this study amounted to 46 people. The results of the validity and reliability test indicate that the organizational climate instrument with employee performance is valid and reliable. The research data was processed with the help of SPSS (Statistical Product and Service Solution) version 26. Descriptive analysis was assisted by the SPSS program by first calculating the mean, median, mode and standard deviation of the two variables. Then the normality and linearity tests were carried out using the Product Moment Correlation formula to see the relationship between the two variables. Then, the significance of the relationship between variables was tested using the T test formula. The results of data analysis showed 1) the organizational climate was in a conducive interpretation, namely 88.86%. 2) employee performance is in a fairly high interpretation, namely 88.73%. 3) there is a significant relationship between the two variables with a correlation coefficient of 0.818 and a correlation significance test of 9.437, and, r² = 66.91%. Based on the results of the study, it can be concluded that organizational climate is one of the factors that affect employee performance at a correlation value of 0.818 with a contribution of 66.91%. This means that the better the organizational climate, the higher the employee's performance.